Aplikasi Surat Jalan Berbasis Android - Lie, Steven; Wella, Wella; Tjahjana, David (Maranatha University Press, 2024)
In the digital era with high internet penetration and rapid e-commerce growth, the need for digital solutions to increase business efficiency is increasingly urgent. The Android-based travel letter application is here as the right solution to help the sales team manage tasks, track and create reports easily and efficiently. This application offers various benefits, such as easier mobility, efficiency with automation features, increased productivity, and closer consumer relationships. Features such as a camera to upload proof of travel documents, search to make it easier to find travel documents, and travel history to view travel history of travel documents, further increase the value of this application. This application development uses the prototype method and has been tested with user acceptance testing (UAT) and user satisfaction surveys. The results show that 95.3% of the 95 UAT respondents and 99.6% of the 35 survey respondents were satisfied with the application performance. This shows that this Android-based travel document application is suitable for use and can help improve company performance.